THE OPTIMIZATION OF THE RESULTS OF CHEMICAL MUSCLE DENERVATION THROUGH THE RECONSTITUTION OF BOTULINUM TOXIN TYPE A IN A STERILE INJECTABLE PHYSIOLOGICAL VEHICLE ENRICHED WITH ZINC - Antonio Matrone, Marco; Maria Gomes da Costa, Marcia; Capelli Barca, Marília; Rodrigues Matrone, Taynan; Ikeoka, Kiroit; Carneiro Silva, Suellen; Cruz Vieira, Darlene; Nogueira Porto, Alessandra (Health and Society, 2022)
Botulinum toxin type A (TBA) is the most potent neurotoxin from the eight produced serotypes by the anaerobic gram-positive bacteria Clostridium Botulinum. To affect exclusively the nervous tissue, it is classified as neurotoxin. Its action promotes, within the presynaptic ending nerves, by blocking of the release of neurotransmitters, including acetylcholine. This nervous terminal incapacitation by the destruction of the SNAP25 protein binding loops in the SNARE complex is permanent. Labeled as Chemical Muscle Denervation, this non-invasive technique of significant relevance has aroused the interest of professionals and researchers from various areas and promoting a growing offer of new commercial options, protocol variations and clinical trials, in the aesthetic and therapeutic-functional segment. However, it has been observed lately a dissatisfaction of both professionals and patients, regarding the duration of the effects of the toxin, a reason that directly interferes with the interval between sessions, patient comfort and operating cost of treatments. When searching in the basic literature for concepts and justifications for the technical unpleasantness, in an integrated and interrelated way, it was observed that, as in any chemical phenomenon, chemical muscular denervation needs an ideal scenario. The pH level outside the proper standard at the TBA application site or the saline solution itself where the toxin was reconstituted, the sufficiency of zinc molecules for zinc-dependent reactions or even the choice and execution of protocols are simple examples of this need. The new literary focus brought as a diagnosis the existence of technical gaps, named in this study as “GAPs”, and which directly interfere in the success of procedures, when not identified and corrected. Two of these gaps, pH and zinc level will be presented and resolved in this article.